2020
DOI: 10.1177/1059601120917589
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Leader Back in: Why, How, and When Leadership Empowerment Behavior Shapes Coworker Conflict

Abstract: With the diffusion of team-based work organizations and flatter organizational hierarchies, many leaders empower employees to perform their work. Empowerment creates an interesting tension regarding coworker conflict, enhancing trust and giving employees more autonomy to prevent conflict, while also increasing workload and the potential for coworker conflict. Recent conflict research has focused on how characteristics of individuals, groups, and tasks contribute to conflict among coworkers. We extend this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…An avenue for future research is the investigation of unfairness and conflict dynamics in the leader-member relationship (Giacomantonio et al, 2011;Ismail et al, 2012;Adamovic et al, 2020). In contrast, to the relationship between team members, the leader-member relationship is characterized by power and status differences.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…An avenue for future research is the investigation of unfairness and conflict dynamics in the leader-member relationship (Giacomantonio et al, 2011;Ismail et al, 2012;Adamovic et al, 2020). In contrast, to the relationship between team members, the leader-member relationship is characterized by power and status differences.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…One of the core mechanisms contributing to relationship quality at work is the presence or absence of relationship conflict (Frone, 2000). Conflict researchers have highlighted the deleterious effects of relationship conflict for employees and organizations (Adamovic et al, 2020;Jehn, 1995). According to a recent FlexJobs survey of 4,612 job seekers, 73% of respondents indicated that they would quit or not accept a position if it had a toxic culture, one of the proxies for a work environment riddled with relationship conflict (Pelta, 2021).…”
mentioning
confidence: 99%
“…Others contribute to conflict dynamics by tracing the trajectories using a longitudinal design (e.g., Thiel et al, 2019). The third stream of team conflict research has focused on conflict induced by some new practices in modern organizations, such as shared leadership and leadership empowerment (e.g., Adamovic et al, 2020; Sinha et al, 2021).…”
Section: Resultsmentioning
confidence: 99%